Społeczne konsekwencje zaburzenia komunikacji dzieci ze spektrum autyzmu = Social consequences of communication disorder in the Autism spectrum - Famuła-Jurczak, Anita (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The functioning of the individual in the world is inextricably linked to interaction with another person. How we read the messages broadcast by another person depends on our ability to understand messages and recognizethe emotional states and intentions of our interlocutor.
Keywords: komunikacja; rozwój; spektrum zaburzeń autystycznych; communication; development; autism spectrum disorder